Translanguaging Practices in Multilingual Young Learners' Classroom: In a Child Development Center in Thailand - Isra Risky Amanda; Faizatul Husna; Sari Diana (Lembaga Teewan Journal Solutions, 2026)
This study aims to explore translanguaging practices in multilingual classrooms involving young learners. Using a qualitative approach, data were collected through classroom observations and semi-structured interviews with five teachers. The findings reveal that translanguaging is consistently used as part of the teaching and learning process. Teachers employ multiple languages—English, Malay, and Thai—within a single learning activity to accommodate students’ diverse linguistic backgrounds. Language shifting is used strategically to clarify concepts and vocabulary, while repetition of instructions in different languages helps ensure students’ understanding. In addition, students respond using mixed languages, indicating that translanguaging occurs naturally in classroom interaction. The study also finds that translanguaging plays significant pedagogical roles, particularly in enhancing students’ comprehension, confidence, and participation. The use of students’ first language creates a more inclusive and supportive learning environment, allowing them to engage more actively in classroom activities. These findings suggest that translanguaging is not merely a communicative practice but also an effective pedagogical strategy in multilingual early childhood education.